Tax Incidence in a Growing Economy with Variable Factor Supply - Feldstein, Martin S. (Quarterly Journal of Economics, 1974)
I. A one-sector general equilibrium analysis, 553. — II. A numerical example, 560. — III. Long-run incidence in a growing economy, 563. — IV. The path of adjustment, 570. — V. Conclusion, 572.